2019
DOI: 10.1002/jlcr.3702
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of [15N4] purine labeled cytokinin glycosides derived from zeatins and topolins with 9‐β‐d, 7‐β‐d‐glucopyranosyl, or 9‐β‐d‐ribofuranosyl group

Abstract: Synthesis of [ 15 N 4 ] purine labeled cytokinine glycosides derived from zeatinsand topolins containing a 9-β-D, 7-β-D-glucopyranosyl, or 9-β-D-ribofuranosyl group is described. These N 6 -substituted adenine derivatives are intended as internal analytic standards for phytohormone analysis. All labeled compounds were prepared from 6-chloro[ 15 N 4 ]purine (1). The equilibrium reaction of 1 with acetobromo-α-D-glucose gave isomeric 7-β-D (3) and 9-β-D (4) chloro glucosyl precursors, which were treated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…In the most promising report in the literature, peracetylated 6-chloro-7-(β- d -glucopyranosyl)­purine ( 3a ) was isolated in 60% yield by the modified Vorbrüggen method . However, we found that the NMR data they reported for the prepared compound corresponded to N 9 -isomer 4a and thus were consistent with the spectra of the N 9 -isomer in other reports where the NMR spectra of both isomers were provided. ,, Additionally, analogous N 7 -galactosyl 3d and mannosyl 3e derivatives were incorrectly described in this paper, which was verified experimentally in our work.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In the most promising report in the literature, peracetylated 6-chloro-7-(β- d -glucopyranosyl)­purine ( 3a ) was isolated in 60% yield by the modified Vorbrüggen method . However, we found that the NMR data they reported for the prepared compound corresponded to N 9 -isomer 4a and thus were consistent with the spectra of the N 9 -isomer in other reports where the NMR spectra of both isomers were provided. ,, Additionally, analogous N 7 -galactosyl 3d and mannosyl 3e derivatives were incorrectly described in this paper, which was verified experimentally in our work.…”
Section: Resultssupporting
confidence: 86%
“…Generally, the N 7 position of the glucosyl group in prepared 6chloro-7-(β-D-glucopyranosyl)purine 3a was confirmed by comparison of 1 H and 13 C NMR data with identical compounds prepared in two different ways. 18,33 Moreover, the regioselectivity of the glycosyl group in the purine skeleton of prepared compounds 3 and 5 was also solved after assigning 1 H and 13 C signals to the corresponding atoms in the molecule. The chemical shifts of the single 13 C atoms across all of the prepared N 7 -nucleosides (3 and 5) of 6-chloropurine and 2,6-dichloropurine correlated and were essentially preserved.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracted cytokinin sample in the lane had the same Rf value as the cytokinin reference standard (Kinetin). The findings are consistent with prior findings from our lab and other authors [17,24,30].…”
Section: Detection Of Cytokinin By Thin Layer Chromatographysupporting
confidence: 94%